Enhanced cellulosic ethanol production via consolidated bioprocessing by Clostridium thermocellum ATCC 31924☆. (February 2018) - Singh, Nisha; Mathur, Anshu S.; Gupta, Ravi P.; Barrow, Colin J.; Tuli, Deepak; Puri, Munish
Graphical abstract: Highlights: Clostridium thermocellum ATCC 31924 was employed for consolidated bioprocessing. Enhanced ethanol production was observed at alkaline pH. 95.32% conversion of crystalline cellulose was obtained. Complete inhibition of lactate production in the presence of acetate. High cellulase and xylanase activities were expressed by purified cellulosomes. Abstract: The production of bioethanol was studied by the cultivation of Clostridium thermocellum ATCC 31924 in MTC medium including crystalline cellulose as the sole substrate. The effects of key operational parameters that affect bioethanol production from microcrystalline cellulose were optimized. Under optimum conditions (pH 8.0, temperature 55 °C, inoculum size 4% (v/v) and 0.5% (w/v) substrate concentration), a maximum ethanol yield of 0.30 g ethanol/g cellulose consumed and 95.32% cellulose conversion was obtained. An inclusion of modest acetate concentration in the medium showed that carbon flux shifted away from lactate accompanied by 20% increase in ethanol production. It suggests that strain ATCC 31924 differed in its cellulose conversion efficacy and optimum pH requirements compared to the other reported strains of Clostridium thermocellum . The purified cellulosome of strain ATCC 31924 found to be rich in both cellulase and xylanase enzymes emphasizing the importance of this strain for the degradation of lignocellulosic biomass.